Impact of Disclosing Labeling Information on Consumer Sensory Evaluation of Ground Beef From a Similar Source - K. M. Harr; E. S. Beyer; K. J. Farmer; S. G. Davis; M. D. Chao; J. L. Vipham; M. D. Zumbaugh; T. G. O'Quinn (Kansas Agricultural Experiment Station Research Reports, 2022)
Objective:The objective of this study was to determine the effect of providing labeling information prior to evaluation on consumers’ palatability ratings of ground beef from a similar source. Study Description:Ground beef (80% lean/20% fat) from a similar source was obtained and fabricated into 0.25 lb patties. Patties were fed to consumers who evaluated each sample for different palatability traits. Consumers (n = 105) were informed about the labeling information of each sample prior to evaluation. Labels utilized: all natural, animal raised without added antibiotics (WA), animal raised without added hormones (WH), fresh never frozen (FNF), grass-fed, locally sourced, premium quality, U.S. Department of Agriculture organic (ORG), and a blank sample (NONE). Results:There were no differences (P>0.05) in consumer ratings for tenderness, juiciness, texture, and overall liking for all labeling terms evaluated. When ground beef was labeled as locally sourced, there were large increases (P<0.05) in consumer ratings for tenderness, juiciness, flavor, texture, overall liking, and purchasing intent. Moreover, labeling ground beef as grass-fed resulted in large increases (P<0.05) in consumer ratings for tenderness, juiciness, flavor, texture, and purchasing intent. Except for grass-fed, overall liking ratings increased (P<0.05) when the additional labeling information was provided to consumers. Additionally, all the purchasing intent ratings increased (P<0.05) when information was provided except for when the ground beef was labeled as premium quality. No differences (P>0.05) were found in the percentage of samples rated as acceptable for tenderness, flavor, and texture for all the labeling terms evaluated. Labeling ground beef as all natural, grass-fed, locally sourced, and premium quality increased (P<0.05) the percentage of samples rated as acceptable for tenderness. For overall acceptability, labeling ground beef as WA resulted in a decrease (P<0.05) in the percentage of samples rated as acceptable. The Bottom Line:Results from this study indicate that consumers’ eating experiences are swayed by the labeling terms found on packages. Those marketing beef products to consumers need to carefully select the marketing materials utilized.
Keywords: consumer; ground beef; labeling